Pelestarian Bahasa Jawa Kromo Inggil dalam Upaya Membentuk Akhlak Siswa Kelas V di UPT SD Negeri Sotang Tambakboyo Tuban - Mardhiyah, Umi Rossy; Choirudin, M.; Faridah, Zeni (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2025)
This study was conducted in response to the decline in students’ moral character, particularly in terms of politeness and the diminishing appreciation of the cultural values embedded in the Javanese kromo inggil language. Early introduction to the Kromo Inggil language has been recognized as an urgent step in preserving the cultural heritage of the Javanese language, as it inherently conveys moral values, character education, and communicative politeness. The primary objective of this research is to implement the Kromo Inggil language culture as a means of sustaining and preserving its continuity at UPT SD Negeri Sotang Tambakboyo, Tuban. This study examines the importance of community interest, specifically among elementary school students, in practicing the kromo inggil language within the school, family, and broader community contexts. These environments play a crucial and significant role in preserving the Javanese kromo inggil language, fostering habitual use, and instilling moral values. The findings of the study indicate that the use of the kromo inggil language among Grade V students has a positive impact on character formation. Students demonstrate improved politeness, greater respect for teachers and parents, and increased familiarity with using refined and respectful language in daily communication.